Movimento dos atingidos por barragens (MAB), a questão ambiental e a participação política - Araújo, Christianne Evaristo de (2006)
During the previous years, but above all starting in the 90’s, researchers have been calling the attention for an emerging field of studies composed by the confluence of environmentalism and social movements, a quite promising political trend since it integrates universalistic demands instead of particularistic ones, as it is the case of the majority of the most contemporary social movements. As this is an emerging field, and therefore a challenging one, I have found it pertinent to propose as an investigation object the relationships between the environmental issue and an specific social movement – the Affected by Dams Movement (MAB), based on the hypothesis that environmental issues should receive a prominent place in the pedagogy and methodology of this movement due to its own political nature. However, considering the research and analysis of the documents produced by the MAB, I have decided to verify through a case study – and using the participating observation as a method – how the relationship between the environmental issue and the political participation was configured in the daily routine of the residents affected by dams. To carry out this verification I have chosen the Castanhão Dam, located in the Middle Jaguaribe, Ceará, and the Novo Alagamar rural resettling, which at the time of the research (2004-2005) had already obtained considerable political results through the support and militancy in the MAB. The data presented and discussed in this work, with the support of current theoretical texts, have confirmed that the environmental theme is very integrated in the ideology of the MAB – either in the identification of problems or in the emergent ways of solving them, this movement has already achieved, in dialogues with similar international movements, to produce a critical reflection on the model of energy and water policies in the current historical moment of the capitalist production way, commonly denominated globalization. This research has also verified that the residents of the Novo Alagamar resettling have an understanding of the environment meaning and environmental education, although they do not use those terminologies produced by the Brazilian institutional culture. All the data obtained through the participating observation – considered as the most appropriate method for the registration of implicit conceptions – have revealed that for the residents of the resettling, the atmosphere is conceived as historicized, that is, inseparable from the human being and social universe.